A single chip for 4-channel LED dimming driver of 240 W true color display with SPI control. (August 2018) - Hsia, Shih-Chang; Ciou, Jyun-Jia; Kuo, Po-Yu
Abstract: LED (Light Emitting Diode) lighting can provide rich colors for many applications such as stage lights and LED display panels. This paper presents a 4-channel LED dimming chip based on SPI(serial parallel interface) and multi-level current control for true color lighting. This chip includes four channels, each of which can drive a current of about 1 A. For four-channel LED dimming, a control of 8-bit PWM is proposed with SPI protocol. To meet any type LED power, the maximum driving current can be easily adjusted by digital switches rather than by changing the sensing resistors. The prototyping chip was designed using TSMC 0.25 μm process, which is the second generator of high-voltage technology, and the resulting chip area with pads is only 1.9 × 2.419 mm 2 . Each channel can drive up to 60 W LED devices with supplying voltage 60 V and driving current 1A. The total driving power can achieve 240 W in maximum. With SPI control, the number of I/O pins can be reduced for multi channels driving. For practical tests, this chip can be controlled by a microprocessor through SPI protocol to adjust the PWM duty of each channel. Experimental results show that the chip can drive a 4-channel COB LED array for true color display.